iLearnTest: Jogo educativo para aprendizagem de testes de software - Tânia Patricia Bernardes Ribeiro (2014)
Games are part of human life since ancient times, being present not only in our childhood but also in other moments. Over the past few years, studies point that the use of games as a supplement to traditional learning is much more efficient than just using the traditional teaching method. Games can be effective educational tools, since as they amuse and motivate, they facilitate learning and increase retention capacity of what was taught, exercising the mind and intellectual thoughts of the player. When games are used to motivate the learning process they are defined as serious games. So, through the use of game mechanisms, iLearnTest was developed, a serious game capable of withstanding the teaching of software testing, transmitting concepts required to obtain the certification ISTQB Foundation, thus allowing the preparation of students for the working world. In an engaging and entertaining way the player has the opportunity to learn at his own self-pace, assimilate theoretical concepts, conduct practical exercises and receive a performance score.